Effect of using different levels of nano-zinc oxide with date by products on in vitro digestibility, fermentation characteristics and gas production - Al-ghazali , Bashar Noori Kadhim; Muhammad, Sondos Farouk (Journal of Kerbala for Agricultural Sciences, 2022)
The experiment was conducted to study the effect of adding different levels of nano zinc oxide (0, 15 and 30 mg) / kg DM to mixture ration consisting of nano-zinc oxide with date by products either 30% date kernel or date peels or mixture (15 date kernel + 15 date peels) to 70% concentrate ration on digestibility, rumen characteristics, total gas and methane gas production. the results showed significant decrease as a result of adding nano-zinc oxide N zno in methane gas production for the treatment 15 and 30 mg/kg, and it reached (16.88 and 15.55 ml/200 mg), and (Date kernel produced significantly more total gas and methane, metabolizable energy (ME), in vitro organic matter digestibility (IVOMD%), and fatty acid short-chain SCFA (45.55, 23.77, 64.14, 11.25, and 1.02), respectively)..( Date kernel produced significantly more total gas and methane, metabolizable energy (ME), in vitro organic matter digestibility (IVOMD%), and fatty acid short-chain SCFA (45.55, 23.77, 64.14, 11.25, and 1.02), respectively. Also, the treatment of adding nano-zinc oxide at the level of 15 mg/kg dry matter significantly was superior to the digestibility factor of dry matter and organic, and it reached 62.29 and 63.96%, respectively, compared to the levels of 0 and 30 mg/kg dry matter and a significant decrease at levels of 0 and 15 mg/kg dry matter, which was 5.31 and 5.15 for pH 26.44 and 30.95 (mg/100ml) for ammonia nitrogen, respectively. whereas significantly increased for the level of 15 mg/kg dry matter, in the total volatile fatty acids and it reached 3.23 (mmol/100ml) after a 24-hour incubation period for the rumen fluid in vitro.